Eu3+-doped lithium tellurite glasses prepared under vacuum condition: Spectroscopic investigation and energy transfer mechanism - Andrade, L. H.C.; Lima, S. M.; Silva, R. A.; Devecchi, M. R.; Moraes, J. C.S. [UNESP]; de Ligny, D.; Nunes, L. A.O. (Elsevier, 2022)
To our knowledge, for the first time Eu2O3-doped lithium tellurite (TL) glasses are synthesized under vacuum conditions. The structural and optical spectroscopic properties are discussed. This investigation shows that the europium doped TL glasses prepared under vacuum (Eu3+-doped TL-vac) present low OH− concentration, which increases the transparency in the visible spectral range due to a decrease in TeO4 unity and an increase of the transparency in the mid-infrared spectral region. The luminescence spectra show several emission bands from superior energy levels 5D0, 5D1, 5D2 and 5D3→7FJ (J = from 0 to 4). Time resolved luminescence experiments allow the observation of the energy relaxation and migration among the 5D3→5D1 to 7F0→7F6 and 5D1→5D0 to 7F0→7F3 energy levels due to Eu3+ ions pairs, reported here for the first time. The Judd-Ofelt analysis of the emission spectrum allowed us to determine the phenomenological parameters Ω2 and Ω4, indicating that Eu3+ presents less covalent characteristics, less compactness than in others tellurite glasses, and a quantum efficiency of the 5D0 energy level of 51%. These results indicate that TL-vac glass doped with rare earths can be promising candidates for new optical devices.
Keywords: Almost OH− Free tellurite glasses D; Energy migration C; Eu3+ ion B; Vacuum condition D